Key Assembling Issues Relating to Mechanical Vibration of Fabricated Rotor of Large Induction Machines - Vladimir Kindl; Miroslav Byrtus; Bohumil Skala; Vaclav Kus (Communications - Scientific letters of the University of Zilina, 2019)
In many applications, where rotating machines of high power are used, high demands on reliability and safety are laid. Precise manufacturing procedures has to be kept even in case of machines retrofits when e.g. rotors are newly assembled. Even small inaccuracies or misguiding the precise technological procedure can lead to improper running of the machine and it can result in shut-down of complete drive. In case of primary circuits of nuclear power plants, it further means the shut-down of the whole power plant. Consequently, it results in significant financial losses (foregone profit and cost given by problem fixing). The paper presents a methodology of vibration origin investigation in case of large rotating machines which are part of drives like pump, compressors etc. The methodology is based on the detection of undesirable vibration using a diagnostic system on-site and further it uses mathematical modelling of corresponding mechanical parts to reveal the vibration origin. The modelling along with the measurement showed that the detected dangerous vibration is caused by misguided assembling of the rotor of the machine.